Foreign Shareholdings Impact on Efficiency of the Acquired Local Banks in Indonesia - Rivai, Aswin; Saksana, Joned Ceilendra; Kusnadi, Kusnadi (Journal of Reviews on Global Economics, 2019)
The motivation of the studies is to investigate the impact of foreign shareholding originated from developed and developing countries on the efficiency of acquired local banks in Indonesia during 2007-2017 by including Corporate Governance as a moderating variable. Methodology: Using the secondary aggregate data of 29 commercial banks acquired by foreign shareholders, a panel regression model using econometrics methods of GLS, and DEA was applied to examine the effects of percentage of foreign shareholdings on efficiency of the acquired local banks. The main findings; First, percentage of foreign shareholdings positively affecting efficiency of acquired local banks only if the foreign shareholders is originated from developed countries. Second, the level of economic advancement of the country of origin of foreign shareholders has significant effects on the efficiency of the acquired local banks. Third, the increase in the size of the Board of Directors tends to decrease the efficiency of the acquired local banks and fourth, the presence of Foreign Director has a positive moderating effect on strengthening the effect of percentage of foreign shareholdings on the efficiency of the acquired local banks. Overall, the originality of this studies is that the percentage of foreign shareholdings and its country of origin are two combined factors that cannot be separated in affecting the level of efficiency of its acquired local bank and the fact of significant positive moderating effect of Foreign Director. As policy consideration, monetary authority need to perform strict due diligence on prospective foreign shareholders specifically originated from developing countries, advise banks to maintain the existence of Foreign Director and to encourage small local banks to be merged prior to the acquisition by foreign shareholders.